Comparison of the forty-eight week efficacy between telbivudine and entecavir in HBeAgpositive Asian patients with chronic hepatitis B: A meta-analysis - Na WANG; Huai-Dong HU; Hang SUN; Qian FENG; Qi LIU; Hong REN (Turkish Journal of Gastroenterology, 2019)
-